PEMISAHAN KROMATOGRAFI PADA FASA TERIKAT DIOl - Julia Kantasubrata (Jurnal Kimia Terapan Indonesia, 1991)
Chromatographic separation could not all be done on silica and alumina, therefore bonded phases have been developed by reacting organochiorosilane with the silanol group of silica. One of the new development of polar bonded phase is diol phase, which is prepared by reacting the silanol group of silica with GOX (glycidoxypropyttrimethoxysilane), Diol phase is widely applicated in TLC and normal phase HPLC. In -reversed phase HPLC, its application is limited, since with eluent containing water, it lasily swelled. Depending on the solute being separated, hidrogen bond,' electron density and basicity play an important role in the retentiop mechanism. Its application on TLC plate make it possible to be used in bidimensional analysis. The application of dial phase is also discussed, eitherfor the exclusion separation of solutes with large molecular weight or for the separation of simple organic compounds such as steroids with normal phase chromatography mechanism.